Synthesis of Novel di Benzo Spiro Bis-Crown-Ether - Lari, Jalil; Moradgholi, Fatemeh; Vahedi, Hooshang; Massoudi, Abdolhossein (Letters in Organic Chemistry, 2015)
This paper focuses on the synthesis of a wide variety of di benzo spiro bis-crown compounds, in good yields using di-phenols, mono tosylates of oligoethylene glycols and caesium carbonate in acetonitrile.
Keywords: pentaerythritol